2018
DOI: 10.1111/dmcn.13662
|View full text |Cite
|
Sign up to set email alerts
|

What causes the encephalopathy of prematurity?

Abstract: encuesta a los miembros de la Academia, incluyendo aquellos que asistieron a la primera reuni on anual (2016). La encuesta recab o informaci on del conocimiento y uso en la pr actica diaria de sistemas de clasificaci on como el GMFCS, MACS, y EDACS (por sus siglas en ingl es) y del Protocolo Australiano de Vigilancia de Cadera (AHSP). 2-5 El 35% respondi o la encuesta (incluyendo 55.6% que participaron en la reuni on 2016). De los encuestados, el 87.7%, 67.7%, 42.5%, y 52.3% conoc ıan la GMFCS, MACS, EDACS, y … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…[1][2][3] The main pathological features of brain WMD in preterm infants are brain atrophy, brain white matter area injury, and periventricular leukomalacia, which is characterized by oligodendrocyte maturation disorder and subsequent myelin sheath dysplasia. [4][5][6] In addition, WMD also damages axon growth, synaptogenesis, and neurogenesis. 7 Recent studies have suggested that the pathogenesis of WMD includes oxidative stress, inflammation, free radical damage, cytokine toxicity, and glutamate excitotoxic damage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] The main pathological features of brain WMD in preterm infants are brain atrophy, brain white matter area injury, and periventricular leukomalacia, which is characterized by oligodendrocyte maturation disorder and subsequent myelin sheath dysplasia. [4][5][6] In addition, WMD also damages axon growth, synaptogenesis, and neurogenesis. 7 Recent studies have suggested that the pathogenesis of WMD includes oxidative stress, inflammation, free radical damage, cytokine toxicity, and glutamate excitotoxic damage.…”
Section: Introductionmentioning
confidence: 99%
“…White matter damage (WMD) is a common type of brain injury occurring in premature infants and is among the main causes of cerebral palsy and cognitive impairment 1–3 . The main pathological features of brain WMD in preterm infants are brain atrophy, brain white matter area injury, and periventricular leukomalacia, which is characterized by oligodendrocyte maturation disorder and subsequent myelin sheath dysplasia 4–6 . In addition, WMD also damages axon growth, synaptogenesis, and neurogenesis 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Alternative research methods such as adaptive platform and umbrella trials are likely required to characterize the effects and efficacy of multidimensional interventions and multicentered collaborative trials of BCRF. 12 We agree with Blomme that the next steps will involve dissecting out components of treatment for evaluation, 4 and this has already begun. Many are supported by systematic reviews, for example home programmes and parent training/coaching.…”
Section: E T T E R T O T H E E D I T O Rmentioning
confidence: 82%